Adnexal Torsion during Pregnancy after Oocyte In Vitro Maturation and Intracytoplasmic Sperm Injection Cycle. (29th June 2010) - Giulini, Simone; Dante, Giulia; Xella, Susanna; La Marca, Antonio; Marsella, Tiziana; Volpe, Annibale
Abstract : We report a case of right adnexal torsion during pregnancy after an oocyte in vitro maturation and intracitoplasmic sperm injection cycle in patient with polycystic ovary syndrome. A 31-year-old woman with a typical clinical disorder of polycystic ovarian syndrome was included in an oocyte in vitro maturation program. Right adnexal torsion occurred two days after embryo transfer, and laparoscopy detorsion was successfully performed with preservation of adnexa. The patient had a full-term pregnancy and delivered a healthy infant at 40 weeks of gestation. To our knowledge this is the first report of adnexal torsion after an oocyte in vitro maturation and intracitoplasmic sperm injection program.